REVISITING FAITH-BASED DIPLOMACY’S EFFECTIVENESS: EASTERN EUROPEAN ORTHODOX CHURCH IN THE 2022 RUSSO-UKRAINIAN CONFLICT - DIANDRA AYU LARASATI (MANU Journal of Humanities, 2023)
This paper aims to address the possible role of the Eastern European Orthodox Church as an alternative channel to ensure fruitful negotiations to end the Russo-Ukrainian war that has still ongoing since 2022. As the majority religion in Russia, Ukraine, and Eastern Europe as a whole, the Orthodox branch of Christianity has a transnational influence on its followers, including prominent political figures in the aforementioned territories. Utilizing qualitative research methods, this paper is written to provide arguments about whether the Orthodox Church, with its immense presence in the belligerents’ spiritual beliefs, will be able to be employed as a channel to end the Russo-Ukrainian war. In this paper, analysis is conducted through the usage of J. W. McDonald’s “The Institute for Multi-Track Diplomacy” (2012) journal article about multi-track diplomacy and D. Johnston’s Faith-Based Diplomacy: Trumping Realpolitik (2003) book about faith-based diplomacy to gauge the Orthodox Church’s potential as a channel of diplomacy between Russia and Ukraine. This paper finds that overall, the Orthodox Church fails to fulfil the criteria that Johnston (2003) posits; one of the most fatal is the organization’s inability to reconcile the belligerents’ deep historical wounds. Due to the Orthodox Church’s traditional role that has always been closely tied to the Russian government, its capability to build an acceptable negotiation channel is severely impeded.